A spatial profile difference in electrical distribution of resting-state EEG in ADHD children using sLORETA. (1st September 2020) - Jouzizadeh, Mojtaba; Khanbabaie, Reza; Ghaderi, Amir Hossein
Abstract: Purpose: In this article, we propose current source density (CSD) as a marker for diagnosis of Attention Deficit and Hyperactivity Disorder (ADHD) children for the first time. Materials and methods: A source localization method (sLORETA) was used to find the source of abnormality in the CSD in electrical distribution of different frequency bands in resting state EEG for the ADHD children in comparison to the normal children using statistical nonparametric mapping (SnPM) test. Resting-state EEG in eye-open (EO) condition was recorded from 13 ADHD and 15 age-matched normal children (aged between 6 and 13). Results: Significant differences were found in the CSD of three frequency bands: delta, theta, and alpha in the parietal lobe, between ADHD and normal groups. Conclusions: Higher CSD in the parietal lobe for ADHD children was found which suggests that an abnormality exists in the parietal lobe of children with ADHD which can be related to the attention shifting problem in these children.